COMPACTION IN A MANTLE MUSH WITH HIGH MELT CONCENTRATIONS AND THE GENERATION OF MAGMA CHAMBERS - Rabinowicz M.; Genthon P.; Ceuleneer G.; Hillairet M. (My University, 2001)
Most compaction models in the partially molten mantle have addressed the case of low intergranular melt concentrations (up to a few percent). Here we develop a mathematical and numerical formalism adapted to the two-dimensional modeling of compaction in mushes with higher melt concentrations (up to a few tens of percents). Experimental data on mantle-like mushes (olivine crystals+basaltic melts) suggest that the mush viscosity depends in a complex way on the melt concentration: three rheological thresholds occur at melt concentrations of about 5%, 20%, and 40%, respectively. The first threshold corresponds to the establishment of full interconnectivity of the intergranular melt, the second to the formation of a very dense suspension of crystals and the last to the development of crystal clusters in the suspension. The present models take into account the stiff and drastic viscosity drops associated with these rheological thresholds. Intergranular melt migration associated with an initial melt pulse generates a horizon of high melt/crystal ratio. If the melt concentration in the initial pulse presents a local excess, the horizon becomes slightly tilted. As a consequence, melt percolates upslope inside the tilted horizon, pools at its summit and generates a ‘pocket-like’ zone. Due to the higher melt concentration, the upward Darcy velocity in the pocket markedly exceeds that in the horizon. The result is that the pocket-like impregnation is rapidly disconnected from the horizon and a new pocket develops at the summit of the partially fragmented horizon. Eventually, the intergranular melt contained in the horizon is completely redistributed into pockets. Increasing the background melt concentration in the mush from 5%, 20%, and 40% leads to an increase of the maximum melt concentration of 10%, 40%, and 100%, in the transient horizons and of 25%, 60%, and 100% in the pockets. These models suggest that magma chambers with a kilometer extent naturally result from the compaction of a mantle mush with an initial melt concentration exceeding 5%.